Cattle select against the invasive grass tall fescue in heterogeneous pastures managed with prescribed fire. (18th February 2019) - Maresh Nelson, Scott B.; Coon, Jaime J.; Schacht, Walter H.; Miller, James R.
Abstract: Tall fescue ( Festuca arundinacea ) is a Eurasian forage grass extensively planted in the United States. However, an endophytic fungus in tall fescue, Epichloë coenophiala, causes health problems in cattle. We predicted that cattle prefer to graze alternative forages when available. We also predicted that cattle use tall fescue more intensively in recently burned areas, as fire can increase forage quality. We tested these predictions in four diverse‐forage pastures in Iowa, comparing use by cattle of tall fescue and four alternative forages (non‐fescue cool‐season grasses, native warm‐season grasses, non‐leguminous forbs and legumes) to their availabilities at the pasture scale. We also examined how tall fescue influences the distribution of grazing at a fine scale (0.1‐m 2 quadrats). Tall fescue was the most abundant forage (46% of plants), but composed only 26% of grazed vegetation. In contrast, legumes composed 12% of available forage but 25% of grazed vegetation. Other forages were used in proportion to availability. At a fine scale, total grazing frequency (proportion of plants grazed) was lower in quadrats containing abundant tall fescue, and higher in quadrats with abundant warm‐season grasses. Grazing frequency of tall fescue and other cool‐season grasses was greatest in recently burned quadrats, but total grazing frequency did not increase after burning. Our results show that although cattle graze tall fescue, particularly following burns, they limit their use of this grass. Given that tall fescue is underused, creates health risks for cattle, and degrades wildlife habitat quality, it may be advisable to reduce tall fescue in pastures.